OP0050 The treatment gap after fracture in osteoporosis patients in sweden. (15th June 2017) - Spångéus, A; Åkesson, K; Ljunggren, Ö; Banefelt, J; Karlsson, L; Ortsäter, G; Libanati, C; Toth, E; Ström, O
Abstract : Background: In Sweden, ∼50% of women and ∼25% of men are expected to suffer an osteoporosis (OP)-related fracture (Fx) during their lifetime, and hip Fx incidence in Sweden is one of the highest worldwide. Despite this, nationally only 12% of patients with Fx are prescribed an OP treatment following Fx. 1 Understanding the reasons for the marked under-treatment of patients with Fx may provide insights into how to improve deficiencies in the management of OP. Objectives: To assess rates of OP treatment initiation within 1 year (<1 yr) following first Fx in treatment-naïve patients with fracture in Sweden and to evaluate the determinants of treatment initiation. Methods: Patients aged ≥50 yrs with any type of Fx were identified from Swedish national registers between 2006–2012 and followed from time of first Fx. Patients who were treatment-naïve at the time of first Fx were included in the analysis. Here, we report OP treatment initiation <1 yr after Fx in the different baseline subgroups considering gender, age, Fx type, steroid use and comorbidities. Results: 258, 827 treatment-naïve patients with a first Fx (68% female; mean age 72.7 [SD 12.9] yrs) were included. Overall, 6.6% of patients initiated OP treatment <1 yr; the proportion was higher in females (8.5%) than in males (2.3%), and was highest in patients aged 70–80 yrs (10.7%) vs other ten-year age groups (mean 5.5%). Patients with a diagnosed vertebral Fx were more likely to start OP treatment (21.2%) compared with non-vertebral Fx (5.6%). The proportion of patients starting OP treatment was higher in patients receiving glucocorticoid (GC) treatment (17%) compared with those not treated with glucocorticoids (6.1%). In general, comorbidities were not positively associated with treatment initiation, except for those indirectly connected to known contributors of Fx risk, i.e. chronic pulmonary disease (GC use) and rheumatoid arthritis (FRAX-algorithm risk factor), which were associated with increased treatment initiation. Although both dementia and dependency are known to be associated with increased risk of Fx, the tendency to initiate treatment was lower in patients with these conditions compared with those without (1.5% vs 6.9% and 2.3% vs 7.4%, respectively). Conclusions: This study confirms the large treatment gap in OP treatment initiation following a first Fx in Sweden; rate of OP treatment initiation was below the post-Fx treatment initiation rate goal of 30% and also lower than the 12% published national indicator for treatment exposure (2015). 1 The proportion of patients initiating OP treatment appears to be somewhat influenced by gender, age, Fx type, GC use, rheumatic disease, dependency and dementia; nevertheless, treatment initiation rates were low. These data highlight the need for significant efforts to improve OP management post Fx in Sweden. References: Swedish Association of Local Authorities and Regions (SKL) and The National Board of Health and Welfare (2015) Öppna Jämförelser 2015, Hälso- och sjukvård vid kroniska sjukdomar. Acknowledgements: Funded by UCB Pharma. Disclosure of Interest: A. Spångéus Consultant for: Amgen, Speakers bureau: Amgen; Eli Lilly, K. Åkesson Grant/research support from: Amgen, Eli Lilly, Ö. Ljunggren Grant/research support from: Amgen, Eli Lilly, J. Banefelt Consultant for: Quantify Research, funded by UCB to conduct this study, Employee of: Quantify Research, funded by UCB to conduct this study, L. Karlsson Consultant for: Quantify Research, funded by UCB to conduct this study, Employee of: Quantify Research, funded by UCB to conduct this study, G. Ortsäter Consultant for: Quantify Research, funded by UCB to conduct this study, Employee of: Quantify Research, funded by UCB to conduct this study, C. Libanati Shareholder of: UCB Pharma, Employee of: UCB Pharma, E. Toth Shareholder of: UCB Pharma, Employee of: UCB Pharma, O. Ström Grant/research support from: Quantify Research, funded by UCB to conduct this study, Consultant for: Quantify Research, funded by UCB to conduct this study